Mutation analysis of common deafness genes among 1, 201 patients with non‐syndromic hearing loss in Shanxi Province. Issue 3 (28th January 2019) - Zhou, Yongan; Li, Chao; Li, Min; Zhao, Zhonghua; Tian, Shuxiong; Xia, Hou; Liu, Peixian; Han, Yaxin; Ren, Ruirui; Chen, Jianping; Jia, Caihong; Guo, Wei
Abstract: Background: Hearing impairment is one of most frequent birth defects, which affects nearly 1 in every 1, 000 live births. However, the molecular etiology of non‐syndromic deafness in China is not well studied. Here, we have investigated the presence of mutations in three genes commonly mutated in non‐syndromic deafness patients in Shanxi Province, which has the highest frequency of birth defects in China. Methods: In total, 1, 201 unrelated non‐syndromic deafness patients and 300 healthy individuals were enrolled. The hearing ability was confirmed by audiologic evaluation. Three major deafness‐related genes ( GJB2, SLC26A4 (PDS), and mtDNA 12S rRNA ) of all individuals enrolled were analyzed by Sanger sequencing. Results: The results showed that GJB2 mutations accounted for 21.23% (255/1, 201) in the patient group, with c.235delC, a hotspot mutation, accounting for 10.99% (132/1, 201). Moreover, 11 new GJB2 mutations were identified. SLC26A4 mutations accounted for 9.33% (112/1, 201) in the patient group, with IVS7‐2A>G as the most prevalent mutation accounting for 4.75% (57/1, 201). In addition, 15 patients (1.25%) were found to carry mtDNA 12S rRNA c.1555A>G mutation, while only two cases had the mtDNA 12S rRNA c.1494C>T. Conclusion: In our research, it was found that c.235delC in GJB2 and c.919‐2A>G (IVS7‐2A>G) in SLC26A4 were the highest frequency pathogenic variants in Shanxi Province. Taken together, our data will enrich the database of deafness mutations and will help clinical diagnosis, treatment, and genetic counseling of hearing impairment. Abstract : Hearing impairment is one of most frequent birth defects. Here, we have investigated the molecular etiology of non‐syndromic deafness patients in Shanxi Province, which has the highest frequency of birth defects in China. In our research, it was found that c.235delC in GJB2 and c.919‐2A>G (IVS7‐2A>G) in SLC26A4 were the highest frequency pathogenic variants in Shanxi Province. Taken together, our data will enrich the database of deafness mutations and will help clinical diagnosis, treatment, and genetic counseling of hearing impairment.